2007
DOI: 10.1002/elsc.200620176
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Resource Management: The Road To Go for Environmental Biotechnology

Abstract: The breakthroughs in microbiology have allowed us to come to terms with the microbial resources present in culture collections and in natural environments. The challenge at present is to manage these microbial resources, particularly when one deals with open systems where the dynamics of microbial ecology are predominant. Hence, to properly address the aspects of Microbial Resource Management (MRM), one needs to handle the questions of who is there, who is doing what with whom and how can one adjust, control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 94 publications
(151 reference statements)
0
87
0
Order By: Relevance
“…Such a high community compositional diversity does not necessarily reflect a similar profile in terms of activity. In principle, few species are required to take care of the entire AD process, while the others are dormant, and will not become active before a change in environmental conditions occurs [52,53]. This was also the case for the results of this study, as a lower richness is observed on RNA level, while the higher evenness relates with a higher degree of functionality [12][13][14]54], although there is no direct dependency of functionality on microbial richness and evenness.…”
Section: Salt Concentration and Time Differentially Impact The Total mentioning
confidence: 50%
“…Such a high community compositional diversity does not necessarily reflect a similar profile in terms of activity. In principle, few species are required to take care of the entire AD process, while the others are dormant, and will not become active before a change in environmental conditions occurs [52,53]. This was also the case for the results of this study, as a lower richness is observed on RNA level, while the higher evenness relates with a higher degree of functionality [12][13][14]54], although there is no direct dependency of functionality on microbial richness and evenness.…”
Section: Salt Concentration and Time Differentially Impact The Total mentioning
confidence: 50%
“…Wastewater microbiology has informed our understanding of community assembly mechanisms (Ofiteru et al, 2010;Wells et al, 2011;Kim et al, 2012), resilience and stability (Werner et al, 2011;Vuono et al, 2014), and identified novel microbes and metabolic pathways (Strous et al, 1999;van Kessel et al, 2015). Translating this knowledge into effective strategies for 'microbial resource management' (Verstraete et al, 2007) remains a challenge due to the high diversity and dynamics in activated sludge bioreactors, even during times of functional stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is also related to the obvious focus on reactions and processes converting organic molecules at the expense of understanding the importance and roles of, and requirements for, TM in anaerobic bioreactors. Verstraete et al [42] review the challenge of managing microbial resources in open and complex, mixed-species communities in the context of dynamic populations and chemical micro-environments. They defined the concept of 'Microbial Resource Management' (MRM), which is analogous to Human Resource Management, and the requirement to handle questions such as 'who is there', 'who is doing what with whom' and 'how can one adjust, control and/or steer these mixed cultures and communities'?…”
Section: Trace Metal Microbiology and Microbial Ecologymentioning
confidence: 99%
“…They defined the concept of 'Microbial Resource Management' (MRM), which is analogous to Human Resource Management, and the requirement to handle questions such as 'who is there', 'who is doing what with whom' and 'how can one adjust, control and/or steer these mixed cultures and communities'? Just as with the grand challenges of MRM, as outlined by Verstraete et al [42], such as controlling greenhouse gas emissions from natural environments, or managing the human gut microbiome, similarly provocative questions should be considered as to how the availability of TM impacts the management of microbial communities in anaerobic biotechnologies. The use of TM to manage microbial community structure in the AD context is given support by the study of Feng et al [37] demonstrating microbial shifts in response to varying concentrations and combinations of TM.…”
Section: Trace Metal Microbiology and Microbial Ecologymentioning
confidence: 99%